Fabrication of monodisperse nitrogen-doped carbon double-shell hollow nanoparticles for supercapacitors. Issue 33 (10th April 2017) - Yun, Juyoung; Jun, Jaemoon; Lee, Jungsup; Ryu, Jaehoon; Lee, Kisu; Yu, Haejun; Jang, Jyongsik
Abstract : A supercapacitor based on nitrogen-doped carbon double shell hollow nanoparticles as the electrode material exhibited a high specific capacitance of 202 F g −1 at a current density of 0.5 A g −1 due to high surface area and nitrogen-doping. Abstract : Nitrogen-doped carbon double-shell nanoparticles (NC DS-HNPs) were fabricated using SiO2 /TiO2 double-shell nanoparticles (ST DS-HNPs) and polydopamine-coating. The NC DS-HNPs have a high surface area of 873.52 m 2 g −1 and a pore volume of 2.86 cm 3 g −1, which are favorable characteristics for supercapacitors. In addition, nitrogen doping induced pseudo-capacitance via the redox activity of the surface functionalities. A specific capacitance of 202 F g −1 was achieved for supercapacitors based on NC DS-HNPs at a current density of 0.5 A g −1 . Consequently, the unique morphology and electrochemical properties of NC DS-HNPs show great potential for future energy-related devices.